Analysis of Customs Implementation on Export and Import Products - Risky Alfandi Nasution; Edi Marjan Nasution; Lily Muthia Arini; Salsa Billah; Siti Sarah; Monita Rangkuti; Saidah Rihalah; Mulia Rifky; Selvi Adelina; Nur Hayani Lubis; Mhd Erwin Saputra; Mhd Avif Rahman (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the application of customs duties to export and import products by reviewing various aspects, namely customs issues, the definition of customs duties, the legal basis, and examples of export and import products. The main problems that often arise in the implementation of customs duties include bureaucratic obstacles, smuggling, and regulatory uncertainty, all of which can negatively affect the smooth flow of international trade and create challenges for businesses engaging in cross-border transactions. Customs duties themselves are defined as state levies on goods entering (imports) or leaving (exports) the customs area, which function not only as a fiscal instrument to generate government revenue but also as a regulatory tool to control the flow of goods and protect domestic industries. The legal basis for the application of customs duties in Indonesia is regulated by Law Number 17 of 2006 concerning Customs, which provides a clear legal framework for enforcing customs regulations and ensuring compliance by traders and exporters. In practice, customs duties are applied to a wide range of products, including agricultural products, industrial products, consumer goods, and strategic commodities that are critical for national development. Through this analysis, it is hoped that a more comprehensive understanding of the role of customs duties in supporting national economic stability, promoting fair competition, and encouraging healthy, sustainable, and equitable international trade can be achieved, providing valuable insights for policymakers, business actors, and stakeholders in the trade sector.